(untitled) (Actualité en allergologie et en immunologie au Canada, 2025)
Chronic spontaneous urticaria (CSU) is increasingly recognized as a complex immune-mediated disorder, driven by interactions among T cells, mast cells, and inflammatory mediators. This paper summarizes the latest advances in urticaria treatment and management, incorporating new targeted therapies and evidence-based clinical guidelines.